2013
DOI: 10.1021/nn401725a
|View full text |Cite
|
Sign up to set email alerts
|

Monoliths of Semiconducting Block Copolymers by Magnetic Alignment

Abstract: Achieving highly ordered and aligned assemblies of organic semiconductors is a persistent challenge for improving the performance of organic electronics. This is an acute problem in macromolecular systems where slow kinetics and long-range disorder prevail, thus making the fabrication of high-performance large-area semiconducting polymer films a nontrivial venture. Here, we demonstrate that the anisotropic nature of semiconducting chromophores can be effectively leveraged to yield hierarchically ordered materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
74
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 41 publications
2
74
0
Order By: Relevance
“…Work by Weber et al showed that samples, poly(styrene‐ b −4‐vinylbenzyl alkylimidazolium bis(trifluoromethane sulfonlyl)imide) [PS‐ b ‐PVBn‐(alkyl)ImTFSI]), prepared by solvent‐casting and melt‐pressing strongly affect the copolymer conductivities due to the long‐range ordering of polymer morphologies (well‐ordered solvent‐cast film showed higher conductivity than poorly ordered melt‐pressed film) . Additionally, Osuji and coworkers used magnetic field alignment to control the nanoscale structure in BCPs, and their highly aligned samples demonstrated an order of magnitude improvement of ionic conductivity compared to unaligned counterparts by reducing microstructural tortuosity . Their work showed that the ionic conductivity of BCPs strongly is influenced by both the alignment of block domains and the domain orientation.…”
Section: Challenges and Outlookmentioning
confidence: 99%
“…Work by Weber et al showed that samples, poly(styrene‐ b −4‐vinylbenzyl alkylimidazolium bis(trifluoromethane sulfonlyl)imide) [PS‐ b ‐PVBn‐(alkyl)ImTFSI]), prepared by solvent‐casting and melt‐pressing strongly affect the copolymer conductivities due to the long‐range ordering of polymer morphologies (well‐ordered solvent‐cast film showed higher conductivity than poorly ordered melt‐pressed film) . Additionally, Osuji and coworkers used magnetic field alignment to control the nanoscale structure in BCPs, and their highly aligned samples demonstrated an order of magnitude improvement of ionic conductivity compared to unaligned counterparts by reducing microstructural tortuosity . Their work showed that the ionic conductivity of BCPs strongly is influenced by both the alignment of block domains and the domain orientation.…”
Section: Challenges and Outlookmentioning
confidence: 99%
“…LC orientation affects the microdomain orientation because of the anchoring of mesogenic units on the microdomain interface. Side‐chain (SC) LC segments repel amorphous segments to form microdomains and stretch the backbone perpendicular to the interface accompanied by arrangement of the mesogens in the SCs parallel to the interface . A magnetic field can align amorphous microcylinders as well as the LC director of the matrix along the field direction throughout the specimen .…”
Section: Introductionmentioning
confidence: 99%
“…Side‐chain (SC) LC segments repel amorphous segments to form microdomains and stretch the backbone perpendicular to the interface accompanied by arrangement of the mesogens in the SCs parallel to the interface . A magnetic field can align amorphous microcylinders as well as the LC director of the matrix along the field direction throughout the specimen . Smectic (Sm) LCs under shear flow arrange the director in either the velocity gradient or in neutral directions; thus, the microcylinders immersed in an Sm LC matrix compromise on their orientation, arranging their long axis in either the velocity‐gradient or neutral directions even though shear flows usually arrange microcylinders parallel to the flow direction .…”
Section: Introductionmentioning
confidence: 99%
“…Block copolymers incorporating a liquid crystal (LC) segment are designated as LC block copolymers and have attracted attention because their microdomain orientation correlates to the LC orientation owing to the anchoring of mesogenic units on the microdomain interface. Most LC block copolymers have the side‐chain‐type LC segment, which tends to stretch the backbone perpendicular to the interface and arrange the mesogens in the side chains parallel to the interface . Owing to the homogeneous anchoring of mesogens at the interface, a magnetic field can align the amorphous cylinder as well as the LC director along the field direction throughout the specimen .…”
Section: Introductionmentioning
confidence: 99%